2019
DOI: 10.1177/2233865919846727
|View full text |Cite
|
Sign up to set email alerts
|

To cover or not to cover: Alexei Navalny in Russian media

Abstract: This article analyses the discourse about the opposition politician Alexei Navalny in Russian media. Navalny has been actively engaging with his audience through social media and online platforms; however, some media continue to ignore the politician, practically not covering his activities. The article analyses the intensity and sentiment of the media coverage of Navalny based on data from Medialogia. It is concluded that the media in general do cover the politician’s activities and attempts to deliberately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(49 reference statements)
0
4
0
1
Order By: Relevance
“…Another way for a non-democratic country to control the media narrative is by eliminating opposition leaders' participation in the public discourse and reducing the amount of attention they receive from mass media (Kazun 2019 ). However, after recent political protests and governmental intervention in traditional mass media, a large portion of the Russian audience has been attracted by the freedom of speech and lack of censorship on the Internet and social media.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way for a non-democratic country to control the media narrative is by eliminating opposition leaders' participation in the public discourse and reducing the amount of attention they receive from mass media (Kazun 2019 ). However, after recent political protests and governmental intervention in traditional mass media, a large portion of the Russian audience has been attracted by the freedom of speech and lack of censorship on the Internet and social media.…”
Section: Related Workmentioning
confidence: 99%
“…In 2013, Navalny received 27.24% of the vote in the Moscow mayor elections and got the second place after the current mayor of Moscow Sergey Sobyanin, while in 2016 he announced his intention to run in the Russian presidential election in 2018: "It can be concluded that Alexei Navalny is already a sufficiently famous federal-level politician" (Kazun 2019 ). However, the Central Election Committee announced that Navalny was not eligible to run in the 2018 election due to a conviction preventing him from participating until after 2028.…”
Section: Related Workmentioning
confidence: 99%
“…[79]) or media coverage of Alexei Navalny (e.g. [80]). Since these studies utilised a mixture of data sources, potentially this type of data can be used in all possible research directions.…”
Section: The Applications Of Sentiment Analysis For Russian Langumentioning
confidence: 99%
“…Kazun analysed the intensity and sentiment of the media coverage of Alexei Navalny 21 based on data from Russian mass and social media from 2014 to 2016 [80]. Using Medialogia, the authors accessed more than 145,000 news items about Navalny from national newspapers, online media sources, and the three largest federal TV channels.…”
Section: G Mixed Data Sourcesmentioning
confidence: 99%
“…С другой стороны, данный вопрос просто не мог быть оставлен за рамками повестки дня. В ряде случаев, например, при освещении деятельности оппозиции, российские телевизионные каналы игнорируют происходящие события и отдельные личности (Kazun, 2019). Однако в отношении реформы пенсионной системы у населения могло сформироваться мнение, основанное на личном опыте и историях знакомых.…”
unclassified